Identification of miRNAs Involved in Intracranial Aneurysm Rupture in Cigarette-Smoking Patients - Hanbin Wang; Luxuan Wang; Yanli Tan; Chuan Fang; Chunhui Li; Lijian Zhang (Neurology and Therapy, 2023)
Abstract Introduction Smoking is an independent risk factor for the formation and rupture of intracranial aneurysms (IA). However, the underlying mechanism remains unclear. Methods In this study, we performed miRNA sequencing on plasma from 10 smoking patients with IA, 10 non-smoking patients with IA, and 10 healthy controls. The differentially expressed miRNAs (DE miRNAs) between smoking and non-smoking patients with IA were identified. Functional and pathway enrichment analysis is employed to investigate the potential functions of those DE miRNA target genes. The correlations with the clinical parameters were assessed using receiver operating characteristic curve (ROC) analysis. Results In total, we identified 428 DE miRNAs. Functional enrichment analysis showed the target genes were significantly enriched in biological aspects related to cell characteristics, such as cell cycle, cell differentiation, and cell migration. Pathway analysis showed DE miRNAs mainly enriched in the PI3K-Akt signaling pathway, Focal adhesion, and JAK-STAT signaling pathway. The expressions of miR-574-5p, miR-151a-3p, and miR-652-3p correlated well with aneurysm parameters. The AUC of miR-574-5p, miR-151a-3p, and miR-652-3p were 97%, 92%, and 99%, respectively. Conclusion Our study indicated that smoking significantly altered the plasma miRNA profile in patients with IA. The expression of miR-574-5p, miR-151a-3p, and miR-652-3p correlated with aneurysm parameters, which may play a significant role in the formation and rupture of IA.